Rancang Bangun Aplikasi Penentuan Vendor Pernikahan Pelanggan Untuk Usaha Wedding Organizer Menggunakan Metode SMARTER Berbasis Web - Cahyo, Fachreza Ilham Dwi; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Intimate Production (IP) is one of the startup that works on online wedding Organizer in Surabaya. Now, IP is working on service that helps bride and groom and their familiy to plan and manage wedding of their dream. From targeted customers that has been chosen, customers encountered some difficulty when it comes to choose what vendor that they really want, because so many option and the price and quality also have many variety. Moreover, IP offered some chances for the vendor, like: 1) Give a convenience  to choose vendor for customers, 2) Give a cost estimation for the event, 3) As a media for the vendor to grow their potential. IP as a bridge for vendor and customer, as they are joining IP, vendor will get many benefits like receiving many orders from customers that have used IP service. The solution that will be created is a web-based application to play a role as media for vendors to give their offers for customers. Meanwhile, the customers can pick a wedding vendor with choosing what package that was provided by the system from criteria and budget by customer’s input, so customer no need to be confused for choosing what vendor is the best for their wedding.